Influence of narrative settings on learning success in virtual reality games – a case study with “Bridge of Knowledge VR” - Jahn, Katharina; Suren, Markus; Sanchez-Stockhammer, Christina; Rey, Günter Daniel (Frontiers in Virtual Reality, 2025)
Gamification has received increasing attention in research and practice. Although narrations as gamification design elements are frequently implemented into gamified systems, specific content- and context-related design elements of narrations are only scarcely addressed. In this study, we varied the content of the narration for a gamified virtual reality learning system by addressing either a self-oriented (finding a treasure) or other-oriented (rescuing a person) motivational orientation. Further, we varied the context of the narration by using a similar or dissimilar setting of the narration compared to a subsequent virtual reality learning setting. The results of a 2 (motivation: self-oriented vs. other-oriented) × 2 (context: similar vs. dissimilar) between-subjects experiment with a control group show that using an other-oriented motivational orientation in contrast to a self-oriented one increases intrinsic motivation and germane cognitive load, although we could not find evidence for improving learning performance for any of the independent variables. These results imply that implementing rescues in narrations of serious games can be beneficial to foster engagement for language learners.